The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.jcv.2015.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of respiratory syncytial viruses infecting children reported to have received palivizumab immunoprophylaxis

Abstract: Although RSV PZ resistance mutations were infrequent, most RSV-associated illnesses in children with a history of PZ receipt were not due to strain resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 20 publications
0
4
0
2
Order By: Relevance
“…Despite relatively rare usage of the antibody and the highly conserved nature of its viral protein target, resistance has been reported due to variations in the fusion protein binding site. [64][65][66][67][68] One study 69 investigated the human monoclonal antibody MPE8, which cross-neutralises respiratory syncytial virus and human metapneumovirus by binding to two highly conserved anti-parallel β-strands on the pre-fusion viral fusion protein. The investigators found naturally occurring antibodies with this same target specificity in some patient serum samples, and therefore proposed this pre-fusion viral fusion protein as a potential vaccine candidate.…”
Section: Antiviral Drug and Vaccine Developmentmentioning
confidence: 99%
“…Despite relatively rare usage of the antibody and the highly conserved nature of its viral protein target, resistance has been reported due to variations in the fusion protein binding site. [64][65][66][67][68] One study 69 investigated the human monoclonal antibody MPE8, which cross-neutralises respiratory syncytial virus and human metapneumovirus by binding to two highly conserved anti-parallel β-strands on the pre-fusion viral fusion protein. The investigators found naturally occurring antibodies with this same target specificity in some patient serum samples, and therefore proposed this pre-fusion viral fusion protein as a potential vaccine candidate.…”
Section: Antiviral Drug and Vaccine Developmentmentioning
confidence: 99%
“…While the impact that widespread use of anti-RSV F MAbs will have on the emergence and transmission of resistant variants is unknown, these variants may also arise naturally in the absence of drug selection pressure. To date, palivizumab resistance-associated polymorphisms have been rarely observed in circulating RSV strains ( 35 ). Consistent with these reports, the restricted use of palivizumab (Synagis) ( 7 ), and the growth disadvantage of resistant variants in the absence of palivizumab selective pressure ( 36 ), we observed no known palivizumab target site II polymorphisms among 2017–2018 RSV strains.…”
Section: Discussionmentioning
confidence: 99%
“…Наличие антигенных вариаций в F-белке циркулирующих вирусов оценивают с помощью F-специфичных МКА [27,28]. Панель полученных нами разнонаправленных МКА к F-белку позволила оценить антигенную вариабельность изолятов РСВ из Санкт-Петербурга в разработанном варианте мк-ИФА.…”
Section: Discussionunclassified